Assessment of Fine Aggregates from Different Sources in Ibadan and Environs for Concrete Production (2018)
Assessment of natural sand being used as fine aggregate for concrete production in Ibadan and its environs was carried out. Ten sources (F1 – F10) were selected for the study; four (F5, F6, F7, F8) were river sand sources while six (F1, F2, F3, F4, F9, F10) were burrow pit sand sources. Samples from each source were subjected to sieve analysis, atterberg limit, bulk density, specific gravity, water absorption, sand equivalent, clay lumps and friable particles, amount of materials passing 75μm and organic impurities adopting ASTM standard procedures. Results revealed that sand from river sources met all the criteria for concrete production stated in ASTM standard while sand from burrow pits deviated from limits of the standard in some respects. F10 had water absorption of 2.6% which exceeded maximum 2% specified, F9 was not free from clay lumps and friable particles with a significant value of 6% as against 3% maximum specification. F1, F2, F3, F4, F9 and F10 have more amounts of materials passing the 75μm sieve ranging from 10.8% for F9 to 20.1% for F10 than maximum of 5% in standard specification while F1, F9 and F10 showed an indication of having organic impurities. It is recommended that performance test be conducted on concrete made from burrow pits sand before use for concrete production. The knowledge of this study can be used as a prospecting tool for selecting suitable sand for the production of quality concrete.